2007
DOI: 10.1080/10253890701300904
|View full text |Cite
|
Sign up to set email alerts
|

Increased brain serotonin turnover in panic disorder patients in the absence of a panic attack: Reduction by a selective serotonin reuptake inhibitor

Abstract: Since the brain neurotransmitter changes characterising panic disorder remain uncertain, we quantified brain noradrenaline and serotonin turnover in patients with panic disorder, in the absence of a panic attack. Thirty-four untreated patients with panic disorder and 24 matched healthy volunteers were studied. A novel method utilising internal jugular venous sampling, with thermodilution measurement of jugular blood flow, was used to directly quantify brain monoamine turnover, by measuring the overflow of nora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 43 publications
2
46
0
1
Order By: Relevance
“…Evidence of an increased serotonin turnover in patients with depression and panic disorders was provided in a study that reported an increased 5-hydroxyindoleacetic acid level in the internal jugular venous plasma (30). Using in vivo microdialysis, we demonstrated in rats that conditioned fear stress resulted in increased extracellular serotonin in the medial frontal cortex.…”
Section: Discussionmentioning
confidence: 87%
“…Evidence of an increased serotonin turnover in patients with depression and panic disorders was provided in a study that reported an increased 5-hydroxyindoleacetic acid level in the internal jugular venous plasma (30). Using in vivo microdialysis, we demonstrated in rats that conditioned fear stress resulted in increased extracellular serotonin in the medial frontal cortex.…”
Section: Discussionmentioning
confidence: 87%
“…Since selective serotonin reuptake inhibitors (SSRIs) are potent modulators of brain serotonin (Esler et al, 2007;Goldstein and Goodnick, 1998), behavioral effects of fluoxetine on zebrafish merit further scrutiny. Zebrafish possess a well-developed serotonergic system which makes them an ideal model for such analyses.…”
Section: Serotonergic Systemmentioning
confidence: 99%
“…The results presented in the study by Esler et al (2007) demonstrate a marked increase in central serotonin turnover in people with panic disorder that does not appear to be related to differences in reuptake transporter function (Hood et al , 2005, and a normalisation of 5-HT turnover by successful treatment with the selective serotonin reuptake inhibitor (SSRI) citalopram. As Esler et al suggest, it is not possible to rule out the alternative explanation that the SSRI treatment effects are a consequence of repeated testing, but the decision to design the study in the way that they used was made, quite rightly, on ethical grounds.…”
mentioning
confidence: 94%
“…A possibility is that the higher 5-HT turnover demonstrated in the Esler et al (2007) study does not necessarily equate to increased receptor occupancy. If, however, patients with panic disorder are metabolising 5-HTat a greater rate than controls, then one might see high turnover but low effective occupancy; in keeping with the TD-supported hypothesis that a relative underfunctioning through low levels of synaptic 5-HT are associated with panic.…”
mentioning
confidence: 99%
See 1 more Smart Citation